Majocchi disease in a child - Ozturk Perihan; Ataseven Arzu; Ozturk Unal; Demiroren Kaan; Dagli Ferda (Wolters Kluwer Medknow Publications, 2006)
Majocchi disease, purpuric annularis telangiectodes, is an uncommon pigmented purpuric dermatosis. It is usually observed in young adult males, but is very uncommon in childhood. In this paper, a ten-year-old female patient having very number of annular eruptions, surrounded by petechiae on her legs, diagnosed as Majocchi disease, is presented and discussed and the literature discussed.